Implications of EMU for global macroeconomic and financial stability - Dohring, Bjorn; Temprano - Arroyo, Heliodoro; European Commission : Directorate-General for Economic and Financial Affairs (Brussels : Office for Infrastructure and Logistics in Brussels, 2008)
This paper assesses the implications of EMU for world macroeconomic and financial stability. After reviewing the predictions made by the literature, it looks at the evidence of the first ten years of EMU. In so doing, it distinguishes the effect of EMU from global factors at work since the 1980s, often referred to as "the Great Moderation". The paper concludes that EMU is on the whole having a stabilising effect on the world economy, particularly in neighbouring countries. By helping to stabilise interest rates, inflation and GDP growth in the euro area, EMU has contributed to greater stability of those variables in other advanced countries. There is also evidence that EMU is facilitating international risk sharing and consumption smoothing. Predictions that EMU would increase exchange rate volatility are, in general, not confirmed by the data. However, the amplitude of mediumterm exchange rate swings has increased for some currency pairs. Moreover, there is little evidence so far that EMU has facilitated international policy coordination, partly reflecting the still fragmented representation of the euro area in multilateral fora.
Economic Papers.